1970
DOI: 10.1254/jjp.20.246
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Curariform Activity of Hayatinin Methochloride, an Alkaloid of Cissampelos Pareira

Abstract: Pradhan et al. (1-3) carried out pharmacological and clinical studies on hayatin methiodide from Cissampelos pareira for its muscle relaxant properties. In the present paper the curariform actions of hayatinin methochloride (Fig. 1), the other structurally similar alkaloid from the same plant are being reported.Experiments were carried out on the isolated phrenic nerve diaphragm preparation of the rat and isolated sartorius nerve muscle preparations of the frog (Rana tigrina), for the comparison of the neuro-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[4] Cissampelos pareira is reported to have cardioprotective,[5] hepatoprotective,[6] antioxidant and immunomodulatory,[7] antifertility,[8] antiarthritic,[9] and anti-inflammatory activities. [10] The plant is reported to have phytoconsituents like cissampeloflavone,[11] cissamparine,[12] pareirubrines A and B,[13] hayatinin,[14] and protoberberine alkaloids. [15] No pharmacological investigation in the perspective of antitumor activity has yet been reported on C. pariera .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Cissampelos pareira is reported to have cardioprotective,[5] hepatoprotective,[6] antioxidant and immunomodulatory,[7] antifertility,[8] antiarthritic,[9] and anti-inflammatory activities. [10] The plant is reported to have phytoconsituents like cissampeloflavone,[11] cissamparine,[12] pareirubrines A and B,[13] hayatinin,[14] and protoberberine alkaloids. [15] No pharmacological investigation in the perspective of antitumor activity has yet been reported on C. pariera .…”
Section: Introductionmentioning
confidence: 99%
“…En la Facultad de Medicina Humana de la Universidad de San Martín de Porres, dentro de la línea de investigación de plantas con efecto analgésico y antiinflamatorio, hemos demostrado el excelente efecto antiinflamatorio y analgésico de esta planta, comparable al producido por el Diclofenaco, con la ventaja de que éste no lesiona la mucosa gástrica, sino que la protege de las lesiones producidas por la indometacina, en forma semejante como lo hace la Ranitidina (Castañeda, 2003) 4 . Estudios realizados con alcaloides de otras plantas han demostrado efecto antileucémico (alcaloide s tropoloisoquinolínicos) y acción inhibitoria de los alcaloides bisbenzylisoquinolínicos en la producción de óxido nítrico por los macrófagos activados, lo que podría explicar el efecto antiinflamatorio y analgésico 1,2,17,19,20,21,22,27,28 .…”
Section: Figura N° 01unclassified
“…Pradhan et al carried out pharmacological and clinical studies on hayatin methiodide from C. pareira for its muscle relaxant properties [ 7 ]. Basu et al reported curare like activity of hyatinin methochloride from C. pareira [ 8 ]. Cissamperine and other four bisbenzylisoquinoline alkaloids isolated from C. pareira were found to show significant and reproducible inhibitory activity against human carcinoma of the nasopharynx cell culture (KB) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%